ISOLATION, IDENTEFECATION AND EFFECINCY OF PSEUDOMONAS FLUORESCENS BACTERIA TO TERMITE MICROCEROTERMIS DIVERSUS - Sh. H. Kamil; R. F. ALjasani; H. I. ALShammari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to isolate the bacteria Pseudomonase fluorescens from the termite, locust, and American cockroach in the Iraqi environment and to diagnose it based on morphological, biochemical, and molecular diagnosis using the polymerase chain reaction (PCR), as well as test its pathogenicity and efficacy to termites under laboratory conditions. The results of morphological , biochemical, and molecular diagnosis using polymerase chain reaction (PCR) tests showed the isolated bacterial isolates are similar to P. fluorescens .The results of efficiency of different isolates of P. fluorescens showed that they have a high pathogenicity towards termite workers in laboratory and incubation condition.